2023
DOI: 10.3390/lubricants11030114
|View full text |Cite
|
Sign up to set email alerts
|

Different Behaviors of Friction in Open and Closed Forging Test Utilizing Palm Oil-Based Lubricants

Abstract: Increasing demand for manufactured goods in industries such as automobiles, electronics, construction, and aerospace has motivated researchers to develop sustainable manufacturing processes. Most metal-forming lubricants are not eco-friendly; they may cause substantial chemical emissions and constitute a community threat. Bio-oil lubricants are seen as possible replacements for mineral oil-based lubricants. Computational modelling of the forging process uses the finite element method to accelerate and improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The orientation of test piece is similar to the actual orientation of linear motion machines. 10 Palm oil selected for the experiment is called Super Olein IV64. Super Olein is a RBD.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The orientation of test piece is similar to the actual orientation of linear motion machines. 10 Palm oil selected for the experiment is called Super Olein IV64. Super Olein is a RBD.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, due to the toxic consequences that they pose on the environment because of not being biodegradable, 6,7 alternative lubricants are being sought to avail a more friendly lubricant to the environment. 6,810 The performance of palm oil as a lubricant in a cold metal forming process was tested and evaluated by carrying out plane strain extrusion experiments and experimental analyses using a viscoplasticity method. 10,11 The results confirmed that refined bleached deodorized (RBD) palm olein and palm stearin provided sufficient lubrication performance in the cold work metal forming process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations